Chronic subdural hematoma with mild to moderate symptoms: The effect of initial treatment approach on clinical outcome - Merijn Foppen; Roger Lodewijkx; Mariam Slot; William P. Vandertop; Dagmar Verbaan (Brain and Spine)
Background: The effect of a conservative (wait-and-watch) approach in chronic subdural hematoma (cSDH) patients with mild to moderate symptoms, is poorly studied. Surgical evacuation is effective, but inherently carries the risk of surgical or anesthetic complications. Research question: To assess the effect of conservative or operative (burrhole craniostomy) treatment on clinical outcome, in cSDH patients with mild to moderate symptoms. Methods: This single center, retrospective cohort study included 444 cSDH patients with a Markwalder Grading Scale score 1 or 2, treated between 2012 and 2022. The primary outcomes were complication rate, length of hospital stay and 30-days’ mortality. The results were analyzed using both intention-to-treat and as-treated approaches. Propensity score techniques were applied to adjust for clinical and radiological baseline differences. Results: Of the 114 conservatively treated patients, 49 (43%) crossed-over to surgery. The 330 remaining patients were treated surgically. In the intention-to-treat and as-treated analysis, initial surgery was associated with a higher complication rate (OR 2.02, 95% CI 1.04–3.94; OR 2.87, 95% CI 1.04–7.91) and longer hospital stay (β 2.34, 95% CI 0.15–4.52; β 6.62, 95% CI 3.60–9.64). Conservative treatment was associated with higher 30-day mortality (as-treated OR 0.19, 95% CI 0.06–0.66, favoring surgery), but this was unrelated to cSDH. Conclusion: In this selected cohort of cSDH patients with mild to moderate symptoms, a conservative approach was associated with less complications and hospital stay. For these patients, a ‘conservative treatment first’ regimen may therefore be considered. Corroboration in a prospective cohort with neurological and functional outcomes is warranted.